Honestly Ben - Konigsberg, Bill (New York. NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Ben Carver returns for the spring semester at the exclusive Natick School in Massachusetts determined to put his relationship with Rafe Goldberg behind him and concentrate on his grades and the award that will mean a full scholarship--but Rafe is still there, there is a girl named Hannah whom he meets in the library, and behind it all is his relationship with his distant, but demanding father.
Companion to: Openly straight.
HL 660
Keywords: Gay teenagers -- Juvenile fiction; Homosexuality -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Preparatory schools -- Massachusetts -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Gays -- Fiction; Identity -- Fiction; Sexual orientation -- Fiction; Preparatory schools -- Fiction; Schools -- Fiction; Massachusetts -- Fiction